2017
DOI: 10.1208/s12249-017-0727-z
|View full text |Cite
|
Sign up to set email alerts
|

Stable Co-crystals of Glipizide with Enhanced Dissolution Profiles: Preparation and Characterization

Abstract: Present study deciphers preparation of co-crystals of lipophilic glipizide by using four different acids, oxalic, malonic, stearic, and benzoic acids, in order to achieve enhanced solubility and dissolution along with stability. All co-crystals were prepared by dissolving drug and individual acids in the ratio of 1:0.5 in acetonitrile at 60-70°C for 15 min, followed by cooling at room temperature for 24 h. FT-IR spectroscopy revealed no molecular interaction between acids and drug as the internal structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Similarly, in the case of GPZ-GLU (1 : 2) cocrystals, crystalline peaks were present indicating the formation of cocrystals. All the crystalline peaks of glipizide were seen in formulated cocrystals as supported by a previous study (22). PXRD pattern of pure components and fabricated GPZ-GLU cocrystals has given in Figure 2.…”
Section: Powder X-ray Diffractometer Analysissupporting
confidence: 81%
“…Similarly, in the case of GPZ-GLU (1 : 2) cocrystals, crystalline peaks were present indicating the formation of cocrystals. All the crystalline peaks of glipizide were seen in formulated cocrystals as supported by a previous study (22). PXRD pattern of pure components and fabricated GPZ-GLU cocrystals has given in Figure 2.…”
Section: Powder X-ray Diffractometer Analysissupporting
confidence: 81%
“…Therefore, the attribution of the glipizide DSC peak to a simple melting process is not correct [ 10 , 11 , 12 ]. The calorimetric peak is undoubtedly triggered by a decomposition process, which involves a gaseous product evolution and then a mass loss under the peak.…”
Section: Resultsmentioning
confidence: 99%
“…According to the studies published in the scientific literature, GPZ melts at a temperature higher than 200 °C, and different melting temperatures have been reported [ 10 , 11 , 12 ]. The crystal structure of glipizide has been recently addressed by single-crystal X-ray diffraction data [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 5 ml of samples were withdrawn after specified time interval and analyzed by UV spectrophotometer at 243 nm. 26,27 The dissolution profiles of ZFN and cocrystals were compared by similarity factor according to following equation Where f 2 is similarity factor, n is the number of observations, R t is the average percentage drug dissolved from reference formulation and T t is the average percentage drug dissolved from test formulation. An f 2 value above 50 indicates similarity in two profiles.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Similar studies were reported for cocrystals of glipizide, aceclofenac etc. 26,30 Based on the results, ZFN:nicotinamide cocrystals were further subjected to evaluation and validated.…”
Section: Melting Point and Saturation Solubilitymentioning
confidence: 99%